2017
DOI: 10.4236/fns.2017.89062
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition, Fatty Acid Profile and Mycotoxin Contamination in Several Varieties of Mexican Maize

Abstract: In Mexico maize (Zea mays L.) is an important cereal due to excellent taste and nutritional value. Nutritional content and fatty acid profile has been reported in white maize, however, there are several genotypes natives (red, yellow, black, blue, pinto), and many improved hybrids maize of which little is known. Fumonisins and aflatoxins are mycotoxins present in 25% of the world's cereals, mainly in tropical and subtropical regions around the world. This study presents the analysis of proximate composition (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
1
1
Order By: Relevance
“…Maize generally has high carbohydrates and is a source of calories [27]; hence the analyzed hybrids in this study can be a good source of calories and good quality because the quality of grains is determined by their carbohydrate, protein, and oil content [9]. The proximate composition of the maize hybrids analyzed in this experiment agreed with previous authors [1,2,4,6,8,[28][29][30][31]. Maize quality traits such as carbohydrates, protein, and fat are more affected by the environment than the genotype [9].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Maize generally has high carbohydrates and is a source of calories [27]; hence the analyzed hybrids in this study can be a good source of calories and good quality because the quality of grains is determined by their carbohydrate, protein, and oil content [9]. The proximate composition of the maize hybrids analyzed in this experiment agreed with previous authors [1,2,4,6,8,[28][29][30][31]. Maize quality traits such as carbohydrates, protein, and fat are more affected by the environment than the genotype [9].…”
Section: Discussionsupporting
confidence: 87%
“…Maize (Zea mays L.) is a staple crop, as it is widely consumed across the globe. It has a world production of about 967 million metric tons yearly [2,3], and, due to its taste and availability, maize is regarded as Mexico's most popular cereal crop [4]. It is also referred to as the nutritional backbone in central, southern, and eastern Zambia [5].…”
Section: Introductionmentioning
confidence: 99%
“…Our results on the maize linolenic acid content are consistent with that reported to be 0.65-0.95% in Betancourt et al (2017), while they are below those reported to be 1.31 -2.02% in Akıncı et al (2011…”
Section: Maize Linolenic Acid Content (%)supporting
confidence: 91%
“…Our results on the maize linoleic acid content are above those reported to be 41.84 -50.70% in Betancourt et al (2017).…”
Section: Maize Linoleic Acid Content (%)contrasting
confidence: 49%